2015
DOI: 10.1080/10888705.2015.1034278
|View full text |Cite
|
Sign up to set email alerts
|

Zoo Playgrounds: A Source of Enrichment or Stress for a Group of Nearby Cockatoos? A Case Study

Abstract: There is increasing evidence that in some circumstances, zoo visitors may be aversive stimuli to nonhuman animals housed in zoos. Yet, most previous research has focused on primates with little attention given to numerous other species who are housed in zoos. The focus animal of this project was the cockatoo, a species who has received minimal attention in zoo-based research. Furthermore, although the influence of the zoo setting has become increasingly important in visitor effect studies, this is the 1st stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…We found that high daily total visitor numbers were associated with a slight decrease in behavioral diversity level, whereas there was almost no association between instantaneous behavioral diversity level and crowd size. This offers tentative evidence that lemurs are perhaps stimulated or not bothered by intermittent large groups, but when there are continual large groups of visitors (high daily totals), behavioral diversity is reduced, which could indicate an upper limit of tolerance for visitors, which has been found in some captive bird species (Collins & Marples, 2015;Nimon & Dalziel, 1992).…”
Section: Visitor Variablesmentioning
confidence: 54%
See 1 more Smart Citation
“…We found that high daily total visitor numbers were associated with a slight decrease in behavioral diversity level, whereas there was almost no association between instantaneous behavioral diversity level and crowd size. This offers tentative evidence that lemurs are perhaps stimulated or not bothered by intermittent large groups, but when there are continual large groups of visitors (high daily totals), behavioral diversity is reduced, which could indicate an upper limit of tolerance for visitors, which has been found in some captive bird species (Collins & Marples, 2015;Nimon & Dalziel, 1992).…”
Section: Visitor Variablesmentioning
confidence: 54%
“…A recurring finding from visitor effect studies, which extends to various taxonomic groups, is that the ability to retreat from visitors lessens visitor induced stress (Carlstead & Shepherdson, ; Collins & Marples, ; Hosey, ). Thus, exhibit design is of significant importance when considering visitor effects (Sherwen, Hemsworth, Butler, Fanson, & Magrath, ).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, visitor presence can initiate aggressive or stereotypical patterns of animal behavior and thus be a stressor (e.g., Fernandez, Tamborski, Pickens, & Timberlake, ; Hosey, , ), while at other times they can stimulate cognition and social interaction and thus effectively act as a form of enrichment (e.g., Chamove, Hosey, & Schaetzel, ; Davey, ; Owen ); there are also situations where visitor presence has no discernible effect on behavior (Jones, McGregor, Farmer, & Baker, ; Margulis, Hoyos, & Anderson, ). Effects can vary by species (Collins & Marples, ), time of day (Maia et al, ) and existing levels of enrichment within the enclosure (Carder & Semple, ). The visitor effect can thus be very situation specific such that the findings of one study will not necessarily be directly transferable to other situations or species.…”
Section: Introductionmentioning
confidence: 99%
“…We hope that this paper informs students, researchers and zoo professionals about the array of observational methods available and the suitability of those methods for the research project being planned. Although zoo behavioural research is often formed of small N case studies [89,108], these still yield useful, applicable insights into zoo animal husbandry and management; telling researchers about natural history-based husbandry [109] and informing on populationspecific responses to stressors in the zoo [110], for example. Behavioural data give an important insight into an individual's responses to the environment, allowing easily gained inferences on welfare state, mental and physical health, reproductive potential and growth and development.…”
Section: Discussionmentioning
confidence: 99%